Influence de la charge particulaire sur la filtration d'une population d'huître Crassostrea gigas dans le bassin estuarien de Marennes-Oléron (France) : analyse de deux cycle de marée - Soletchnik, Patrick; Prou, Jean; Heral, Maurice; Barille, Laurent; Razet, Daniel; Guezennec, Loïc (ICES/CIEM CM 1991 / F:53, 1991)
Filtration of oyster population (100 animals) have been followed during 16 days in raceway systems with continuous recorder of the input and output of the raceway for in situ turbidity and fluorescence. Experimental conditions were fluctuated with particulate matter which varied during a tidal cycle from 40 mg.l-1to 300 mg.l-1. During the same period the phytoplanktonic biomass presented synchronous variations form 7 to 20 µg.l-1 bound with sediment resuspension of phytobenthos and oyster biodeposit created by alternating currents. Filtration of oyster population during a neap tide cycle, variated between 1.2 and 2.8I.h-1 by animal for a calculated retention based on turbidity and between 2.4 and 4.8 l.h-1 by animal for a retention calculated with phytoplanktonic biomasses. During a spring tide cycle, oysters filtration varied respectively from 0.7 to 2.4l.h-1 animal and 0.5 to 4.31.h-1 by animal. Filtration of the oyster population fluctuated during the tidal cycle with the load of particulate matter. At higher rate, upper tham 100 mg.l-1 which correspond to phytoplanktonic biomass higher than 7 µg.l-1 filtration decreased. It was clear during the low tide of the spring tide. La filtration d'une population de 100 huîtres a été suivie pendant 16 jours dans un raceway par l'enregistrement en continu à l'entrée et à la sortie du raceway de la turbidité et de la fluorescence in situ. Les conditions expérimentales sont très fluctuantes avec des charges sestoniques qui peuvent varier lors d'un cycle tidal de 40 mg.l-1 à 300 mg.l-1. Parallèlement la biomasse chlorophyllienne présente des variations synchrones de 7 à 20 µg.l-1 associées à la remise en suspension du phytobenthos et des biodépôts d'huîtres, générée par le cycle alternatif des courants. La filtration de la population pendant un cycle de vives eaux, oscille entre 1,2 et 2,8 l.h-1 par animal pour une rétention calculée avec la turbidité et entre 2,4 et 4,8 l.h-1 par animal pour une rétention calculée avec les biomasses phytoplanctoniques. Pendant un cycle ...